Influence of Atmospheric Plasma Jet Pre-Treatments of TiO2 Electrodes on Dye Adhesion and DSSC Cell performance - Sheehan, Stephen; Rahman, Mahfujir; Downling, Denis (International Conference on Plasma Surface Engineering, 2013)
Dye-sensitized solar cells (DSSC) based on nanocrystalline TiO2 were invented by O’Regan and Gratzel in 1991. DSSC are third generation, thin film solar cells. They are photoelectrochemical devices whose operating principle closely resembles the photosynthesis reaction of green plants. There is increasing interest in dye-sensitized solar cells (DSSCs) due to their relatively low cost and ease of manufacture. However, the performance of the DSSC solar cell in many cases is limited by the presence of oxygen vacancy (- Ti3+ defects site) along with surface contamination in the TiO2 electrode. To improve current density and the overall efficiency of the DSSCs surface contamination and surface defects need to be reduced. This study investigated the influence of plasma surface treatments of nanocrystalline TiO2 films on photovoltaic performance of the corresponding DSSCs. Two surface treatments, PlasmaTreat™ an atmospheric air plasma system and a Microwave (MW) plasma system were used for the first time to study the effect of plasma surface treatment of TiO2 on DSSC performance.